Iyo ang Tondo, kanya ang Cavite - Santiago, Pablo (Synergy Home Entertainment, 1990)
This is the story of two men leading similar lives, one from Tondo the other from Cavite. Both loved and respected by their family and neighbors. They will also risk their lives to defend their town's honor even if it means putting their lives at stake. But when their paths cross and a misunderstanding erupts, their friendship is put to the test as punches are thrown and bullets fly.